Monitoring canopy and air temperature of dominant vegetation in tropical semi-arid using bioclimatic model - Galvíncio, Josiclêda Domiciano; Pimentel, Rejane Magalhães de Mendonça (Journal of Environmental Analysis and Progress, 2016)
Typical vegetation of arid environments consist of few dominant species highly threatened by climate change. Jurema preta (Mimosa tenuiflora (Willd.) Poiret) is one of these successful species that now is dominant in extensive semiarid areas in the world. The development of a simple bioclimatic model using climate change scenarios based on optimistic and pessimistic predictions of the Intergovernmental Panel on Climate Change (IPCC) shown as a simple tool to predict possible responses of dominant species under dry land conditions and low functional biodiversity. The simple bioclimatic model proved satisfactory in creating climate change scenarios and impacts on the canopy temperature of Jurema preta in semiarid Brazil. The bioclimatic model was efficient to obtain spatially relevant estimations of air temperature from determinations of the surface temperature using satellite images. The model determined that the average difference of 5oC between the air temperature and the leaf temperature for Jurema preta, and an increase of 3oC in air temperature, promote an increase of 2oC in leaf temperature. It lead to disturbances in vital physiological mechanisms in the leaf, mainly the photosynthesis and efficient use of water.